Protein engineering techniques : gateways to synthetic protein universe - Poluri, Krishna Mohan; Gulati, Khushboo (Springer, 2017)
This brief provides a broad overview of protein-engineering research, offering a glimpse of the most common experimental methods. It also presents various computational programs with applications that are widely used in directed evolution, computational and de novo protein design. Further, it sheds light on the advantages and pitfalls of existing methodologies and future perspectives of protein engineering techniques.
Keywords: Protein engineering -- Methodology.; elektronické knihy; electronic books